The Performance and Strategy of Indonesian's Fisheries: A Descriptive Review - Bashir, Abdul; Ishak, Zulkarnain; Asngari, Imam; Mukhlis, Mukhlis; Atiyatna, Dirta Pratama; Hamidi, Ichsan (International Journal of Economics and Financial Issues, 2019)
This study to analyze the performance and strategy of fisheries in Indonesia. The data used in this study is secondary data during 2011-2016. Source of data from the Ministry of Maritime Affairs and Fisheries (KKP) and Central Bureau of Statistics (BPS). The analytical method used with a qualitative descriptive approach, in addition also, for strategy mapping through the SWOT analysis approach by evaluation of strengths, weaknesses, opportunities, and threats in the fisheries sector. The findings of this study indicate that during 2011-2016, the growth performance of production, consumption, investment, export value, trade balance, and potential fish resources based on Maximum Sustainable Yield has increased significantly. However, in our observation, there are still many weaknesses and threats that must be resolved. For this reason, we formulated a strategy in an effort to overcome weaknesses and minimize these threats in conclusions. Keywords: Fisheries, Production, Consumption, Trade, SWOT Analysis JEL Classifications: Q20; Q22; K24 DOI: https://doi.org/10.32479/ijefi.7188